Pathways for nucleation and growth in confined spaces and at interfaces - Benjamin A. Legg; Yandi Hu; Koishi, Ayumi; Michael Whittaker (Elements, 2025)
Mineral crystallization is central to myriad natural processes from the formation of snowflakes to stalagmites, but the molecularscale mechanisms are often far more complex than models reflect. Feedbacks between the hydro-, bio-, and geo-spheres drive complex crystallization processes that challenge our ability to observe and quantify them, motivating an expansion of crystallization theories. In this article, we discuss how the driving forces and timescales of nucleation are influenced by factors ranging from simple geometric confinement to distinct interfacial solution structures involving solvent organization, electrical double layers, and surface charging effects. Taken together, these ubiquitous natural phenomena can preserve metastable intermediates, drive precipitation of undersaturated phases, and modulate crystallization in time and space.